Sun Xi-miao in T he Biogr aphy of T he Avatamsaka - Sutra - LEE Hyun- Sook (Uisahak, 2005)
This paper aimed to introduce and examine the biography of Sun Xi-miao(孫思邈581-682) which I found in The Biography of The Avatamsaka-Sutra(華嚴經傳記), that Fazang(法藏643-712) wrote in 692 A.D. This document was neglected to understand Sun who was the famous medical writer of the collection of prescriptions, the Bei ji qian jin yao fang(備急千金要方). His life is rather well documented, because he has his own biographies in Jiu Tang shu and Xin Tang shu(新唐書) which cited from Da Tang sin yu(大唐新語), published in 807. But I found several new informations about Sun in The Biography of The Avatamsaka-Sutra, such as he use to be a military medicine in the troops of Li Yuan(李淵) who became the first emperor Kao Tsu(高祖) of Tang dynasty and treat Sun with great favour. This document let us know that the Bei ji qian jin yao fang(備急千金要方) was dedicated to Kao Tsu, known as published in 652 A.D. MY CONCLUSIONS ARE AS FOLLOWS: First, it was written by Fazang in 692 A.D, who was the real establisher of the fraternity of the Avatamsaka in China, for the purpose of encouraging to copy the Avatamsaka-Sutra(華嚴經). According to this biography, Sun made 750 copies to persuade the monks and the peoples, and that's the reason Fazang wrote his biography.Secondly, it was not conveyed to posterity, such as Sun was good looking, tall and use to be the medicine of Kao Tsu and dedicated his medical book to the first emperor. It might be left out for Tai Tsung(太宗)'s sake in the official records, who murdered his brother, the heir apparent to the throne and became the second emperor by himself. On the contrary, it was written in Da Tang sin yu, Jiu and Xin Tang shu that Sun made a prediction that his collection of prescriptions would help the holyman after 50 years from Xuan Di(宣帝578-579) of Northern Chou(北周) Dynasty. Holyman meant Tai Tsung. It shows that Sun's biographies in the Da Tang sin yu, Jiu and Xin Tang Shu were based on the documents that might be fabricated and embellished for Tai Tsung. Thirdly, this biography let us know that Sun wote the Bei ji qian jin yao fang under the circumstances that the epidemic disease was spreaded in Changan at 618 A.D. and the population of Kao Tsu era(618-626) was decreased rapidly. I think that's why he wrote down the medical morals as the first chapter, and the prescriptions about the gynecology and pediatrics as the second chapter.